Capability—The Basis Of Human Power - Toirov Zayniddin; Oymatova Dilorom Ro'zimurotovna (Euro Asian Journal Publishing, 2025)
This article talks about the concept of human ability, its types and development factors. The biological and social foundations of ability, innate and acquired characteristics, as well as methodical approaches to its formation in the process of upbringing and education are analyzed. The author sheds light on the importance of ability in professional activity and pays special attention to the methods of its identification and development in the pedagogical process. The article serves as a useful scientific-theoretical resource for pedagogues, psychologists and specialists working with gifted youth.
Keywords: ability; talent; potential